Chapter L'approccio metodologico - Monturano, Gianluca (Studi e saggi, 2020)
This contribution presents a methodological path tailored to highlight and manage the generating processes of Community-based cooperatives in Italian inner areas. Some quantitative techniques are involved, in particular multivariate statistical techniques, together with text analysis, in order to process the outcomes of a direct survey based on open responses. Moreover, a study of scenario, based on balance sheet data, is proposed, to verify the potential profitability of a new cooperative.